Cobalt catalyzed reduction of aromatic nitro compounds via homogeneous and heterogeneous catalysis - Nurseiit, Alibek (Nazarbayev University School of Engineering and Digital Sciences, 2020)
Catalytic reduction of aromatic nitro compounds to amines via homogeneous and heterogeneous approaches was performed. For homogeneous catalysis the combination of commercially available Co(acac)2 and dpephos ligand (dpephos = bis[(2- diphenylphosphino)phenyl]ether) was effectively employed showing the full conversion of the substrate at room temperature using PhSiH3 and HBPin as reductants. For heterogeneous catalysis, two approaches were used, such as generation of free cobalt nanoparticles from Co(OAc)2 and preparation of three composites derived from commercially available Co(OAc)2 and CoCl2 and surface modified silica. The application of free cobalt nanoparticles showed reduction of nitro compounds with full conversion at room temperature within 20 h. The synthesized cobalt composite materials were subjected to reduction of 2-nitrophenol with NaBH4 in water. Comparative kinetic studies indicated that the composite catalyst derived from Co(OAc)2 has the highest catalytic activity in reduction of 2-nitrophenol with the rate constant of 6.72x10-2 min-1. The transition from homogenous catalysis to heterogeneous approach for an effective reduction of aromatic nitro compounds to amines as well as removal of nitro compounds from aqueous solutions were articulated in the present thesis work.
Keywords: Ultraviolet-visible; UV-vis; Scanning Electron Microscope – Energy Dispersive Spectroscopy; SEM-EDS; tricyclohexyl phosphine; Nuclear Magnetic Resonance; Gas Chromatography - Mass Spectroscopy; Catechol; nanoparticle; Research Subject Categories::TECHNOLOGY